Ancient Near Eastern Thought and the Old Testament : Introducing the Conceptual World of the Hebrew Bible - Walton, John H., 1952- (Grand Rapids, Mich. : Baker Academic, 2006)
This volume provides a thoughtful introduction to the literature of the ancient Near East and a well-considered apology for its importance to exegetical work. John Walton suggests that there are three important roles comparative studies can play in biblical interpretation: critical analysis, defense of the biblical text, and exegesis. He focuses particularly on the third aspect and its importance for preventing misinterpretation through the imposition of modern worldviews. In the main body of the text, Walton offers a thoughtful introduction to ancient Near Eastern literature and the "common cognitive environment" that it provides for understanding the world of ancient Israel. After surveying types of literature, he considers the perspectives they offer on beliefs about gods, religion, the cosmos, people, and history. Throughout his study, helpful comparative sidebars focus on Old Testament interpretation to illumine the continuities and discontinuities between the Israelites and their neighbors. This study provides an excellent introduction to the field of comparative studies and will be an important guide for students, scholars, and clergy who want to make use of extrabiblical resources to enrich their understanding of ancient Israel and its scriptures
Part 1: Comparative Studies -- History and Methods -- Comparative Studies, Scholarship, and Theology -- Part 2: Literature of the Ancient Near East -- Summary of the Literature of the Ancient Near East -- Part 3 Religion -- Gods -- Temples and Rituals -- State and Family Religion -- Part 4: Cosmos -- Cosmic Geography -- Cosmology and Cosmogony -- Part 5 People -- Understanding the Past : Human Origins and Role -- Understanding the Past : Historiography -- Encountering the Present : Guidance for Life--Divination and Omens -- Encountering the Present: Context of Life--Cities and Kingship -- Encountering the Present: Guidelines for Life--Law and Wisdom -- Pondering the Future on Earth and after Death.
Includes bibliographical references (pages 343-350) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Comparative studies; Bible. -- Extra-canonical parallels; Middle Eastern literature -- Relation to the Old Testament; Old Testament - Interpretation and Criticism -- Old Testament Extra - Canonical Parallels; Old Testament - Comparative Studies